Study of drought indices in relation to rice crop Production over some States of India - RAO, G. APPA; DATAR, S. V.; SRIVASTAVA, H. N. (MAUSAM, 1992)
Drought monitoring indices used by India Meteorological Department (IMD) and National Remote Sensing Agency (NRSA) have been discussed in relation to crop estimates during kharif seasons of 1989 and 1990 for some States over India. It was found that index used IMD showed moderate to severe drought over certain areas during certain periods, while NRSA reported non-drought conditions. On the other hand, the preliminary estimated rice crop by the respective States during 1989 suggested higher values in four States and lower in one State, with reference to the mean values based, on the previous eight years data. A high degree of correlation between NRSA and IMD drought indices was found, which agree partially with the yield estimates during 1989.